865The dynamics of SES-related health inequality across the lifecycle and the role of selective mortality. (2nd September 2021) - Petrie, Dennis; Allanson, Paul; Chen, Linkun; Gerdtham, Ulf
Abstract: Background: The positive cross-sectional association between health and SES often strengthens at younger ages before peaking at middle ages and then weakening at older ages. Selective mortality is a possible reason for the weakening relationship at older ages but current evidence for this is limited. Methods: This paper uncovers the changing nature of the inter-dependence between SES and health over the lifecycle by further developing and applying longitudinal inequality decomposition techniques which account for mortality. We examine changes in SES-related health inequality for rolling age cohorts by gender for Australia (using the Household, Income and Labour Dynamics in Australia (HILDA) survey) and the United Kingdom (using the Understanding Society survey). Results: We find for young men in both countries that the simultaneous co-movement in both health and income plays the major role in increasing health inequalities. At middle ages the poor start to lose health more quickly than the rich but at older ages selective mortality plays the major role with the poor more likely to die than the rich which also has an indirect effect of making morbidity losses seem less concentrated among the poor. Conclusions: Selective mortality plays a major role in weakening the relationship between SES and health at older ages. Past studies have missed identifying the full effect of selective mortality. Key messages: SES-related health inequalities accumulate throughout the lifecycle, even in older ages.